Effects of gaseous emissions from the Namakwa Sands Mineral Separation Plant near Lutzville on the adjacent succulent Karoo vegetation : a pilot study - Lukama, Beatice M. K. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Conservation Ecology and Entomology)--University of Stellenbosch, 2006.